Taxonomic novelties in Clusia (Clusiaceae) from Venezuela - Do Nascimento-Jr, José E.; Bittrich, Volker; Amaral, Maria Do Carmo E. (Phytotaxa, 2019)
Although a comprehensive taxonomic treatment of the genus Clusia in the Venezuelan Guayana was published 20 years ago, much taxonomic work remains to be done regarding the genus in the region, including description of new species. In this paper we describe and illustrate five new species of Clusia sect. Oedematopus (Clusia dickinsoniana, C. donramonii, C. peterstevensii, C. punctata and C. tetramera), which are characterized by their small flowers without resin or nectar secretion.